Health-related quality of life in locally advanced hepatocellular carcinoma treated by either radioembolisation or sorafenib (SARAH trial). (September 2021) - Pereira, Helena; Bouattour, Mohamed; Burgio, Marco D.; Assenat, Eric; Grégory, Jules; Bronowicki, Jean-Pierre; Chatellier, Gilles; Vilgrain, Valérie; ,; Assenat, Eric; Delhom-Christol, Elisabeth; Fourcade, Marjolène; et al.
Abstract: Background: The aim of this ancillary study of the SARAH trial is to compare health-related quality of life (HRQoL) in patients with locally advanced or inoperable hepatocellular carcinoma (HCC) treated with transarterial radioembolisation (TARE) or sorafenib. Methods: This study included randomised patients who received either TARE or at least one dose of sorafenib with no major deviation in the protocol and who had at least one QoL follow-up assessment in addition to the baseline evaluation. QoL was assessed from the date of randomisation using the European Organisation for Research and Treatment of Cancer QLQ-C30 questionnaire, until disease progression or other reasons for stopping study participation. Data were analysed using linear mixed and time-dependent models. Results: A total of 285 patients were included (122 and 163, in the TARE and sorafenib groups, respectively). Questionnaire completion rates were similar (77.5% versus 80.4%, in the TARE and sorafenib groups, respectively, p  = 0.25). Longitudinal HRQoL analysis showed a significant treatment and time effects for fatigue and global health status, and significant treatment, time and treatment by time interaction effects for appetite loss, diarrhoea and social functioning. The median time to deterioration for the global health status was 3.9 months (95% confidence interval [CI] 3.7–4.3) versus 2.6 months (95% CI 2.0–3.0) in the TARE and sorafenib groups, respectively. Conclusions: HRQoL was preserved longer with TARE than with sorafenib in locally advanced HCC. These data could be used to optimise management of patients with advanced or inoperable HCC. Highlights: Deterioration for global health status was lower in the TARE group compared to sorafenib. Deterioration in physical functioning was lower in the TARE group compared to sorafenib. Deterioration in role functioning was lower in the TARE group compared to sorafenib. Deterioration in social functioning was lower in the TARE group compared to sorafenib. TARE and tumour burden ≤25% were associated with a lower risk of deterioration.